RESOURCES AND COMPETITIVE ADVANTAGES IN AGRIBUSINESS: SYSTEMATIC BIBLIOGRAPHIC REVIEW OF RBV - Tavares, Bartira de Oliveira [UNESP]; Negreti, Amanda dos Santos [UNESP]; Santini Pigatto, Giuliana Aparecida [UNESP]; Pigatto, Gessuir [UNESP] (Univ Sul Santa Catarina-unisul, 2017)
Agribusiness is important for Brazil, in economic terms, of trade balance and in the generation of employments. However, in a market with intense competition, some companies have advantages over others, in the same segment and sector. This article aimed to identify the types of resources considered as a competitive advantage for the agribusiness sector, according to a systematic bibliographic review, using three scientific bases and combinations of four terms to the agribusiness. The results indicated that, in different segments of the agroindustrial chains and organizations, the human and organizational resources were considered of greater importance.
Keywords: Agribusiness; Systematic Bibliographic Review; Resource Based View; Human Resources; Organizational Resources